VD_FINDINFO Pron / 2015 / 14 vom 29. April 2015 - VD Tribunal cantonal (2015)
DÉCISION D'IRRECEVABILITÉ, MOTIVATION DE LA DEMANDE | 309 let. a CPC (CH), 319 let. a CPC (CH), 321 al. 1 CPC (CH), 337 al. 2 CPC (CH)